Peningkatan Pengetahuan dan Keterampilan Masyarakat Desa Barabung dalam Pengolahan Virgin Coconut Oil (VCO) sebagai Produk Bernilai Ekonomi Tinggi - Riski Arifin; Syaubari (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
This community service program was conducted in Barabung Village to enhance the community’s knowledge and skills in processing coconuts into Virgin Coconut Oil (VCO) as a high-value and sustainable product. The main challenge identified was the community’s limited understanding of efficient, hygienic, and market-oriented VCO production. The program was carried out through educational sessions, technical training, and joint production practices using a simple, energy-efficient natural method. Participants learned the basic concepts of VCO, production stages from grating to oil separation, hygiene application, and proper product storage. The program also highlighted the health benefits of VCO, including immune-boosting properties, making it a healthier alternative to regular coconut oil. The results showed a notable improvement in participants’ knowledge, increasing from 33% in the pre-test to 87% after training. These outcomes demonstrate the effectiveness of hands-on training in strengthening community capacity to develop local resource-based enterprises. This initiative serves as a foundation for promoting economic self-reliance through the sustainable utilization of coconut commodities.